1969
DOI: 10.1002/j.2050-0416.1969.tb06377.x
|View full text |Cite
|
Sign up to set email alerts
|

STRUCTURAL ANALYSIS OF WORT DEXTRINS BY MEANS OF Β-Amylase AND THE DEBRANCHING ENZYME, PULLULANASE

Abstract: Dextrins from a sweet wort, prepared by infusion mashing, were fractionated by paper chromatography according to their molecular weights and further into linear and branched dextrins. Each fraction was treated with j9-amylase and with the debranching enzyme, pullulanase. The products of this enzymic hydrolysis were identified by paper chromatography. From the pattern of oligosaccharides so obtained, structures have been postulated for the dextrins with a degree of polymer ization of 4 to 8 glucose units. The l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

1970
1970
2011
2011

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 17 publications
1
16
0
Order By: Relevance
“…Action of pullulanase confirmed that the /3-amylase-resistant oligosaccharides were in fact singly-branched oligosaccharides for which the most likely structures were then given (Enevoldsen and Bathgate, 1969).…”
Section: Objectives Of the Studiesmentioning
confidence: 81%
See 1 more Smart Citation
“…Action of pullulanase confirmed that the /3-amylase-resistant oligosaccharides were in fact singly-branched oligosaccharides for which the most likely structures were then given (Enevoldsen and Bathgate, 1969).…”
Section: Objectives Of the Studiesmentioning
confidence: 81%
“…There are five fermentable sugars, of which sucrose, fructose and part of the glucose are present in barley malt or produced by hydrolysis of sucrose during mashing, while maltotriose, maltose and to some extent glucose are produced through the action of amylases on starch. Additional sugars (not shown) present in minor quantities are inter alia pentoses (Van Roey, 1954; Gjertsen, 1955) isomaltose (Gjertsen, 1955), panose and isopanose (Bathgate, 1969). With respect to the dextrins with four or more glucose units we have paid attention to some characteristics which appear to be a general trend for most beers.…”
Section: Objectives Of the Studiesmentioning
confidence: 99%
“…Enevoldson and Bathgate 12 , Enevoldson and Schmidt 13 and Bringhurst et al 8 have produced papers summarising the products of the hydrolysis of starch and higher dextrins into fermentable sugars, short chain branched and linear dextrins and oligosaccharides, which contribute greatly to our fundamental understanding of these processes in relation to mashing and fermentation in both brewing and distilling. These give some indication of the structures and properties of both linear and branched dextrins which can help us to appreciate their importance in determining wort fermentability, since some of them are easily degraded to fermentable substrates, while others can only be partially, or slowly degraded, or are limit dextrins and hence cannot be fully hydrolysed by the standard set of starch degrading enzymes (α-amylase, β-amylase and limit dextrinase 8,12,13 ).…”
Section: Hydrolysis Of Dextrins By Enzymesmentioning
confidence: 99%
“…These give some indication of the structures and properties of both linear and branched dextrins which can help us to appreciate their importance in determining wort fermentability, since some of them are easily degraded to fermentable substrates, while others can only be partially, or slowly degraded, or are limit dextrins and hence cannot be fully hydrolysed by the standard set of starch degrading enzymes (α-amylase, β-amylase and limit dextrinase 8,12,13 ). Vriesekoop et al 26 further elucidated the actions and activity of the main starch degrading enzymes α-amylase, β-amylase and limit dextrinase, and describe in some detail the turnover of dextrins during mashing and fermentation of brewing (boiled) and distilling (unboiled) type worts.…”
Section: Hydrolysis Of Dextrins By Enzymesmentioning
confidence: 99%
“…6 The amino acids, alanine, valine and leucine + isoleucine were determined by gas-liquid chromatography according to Olsen.8 Proteolytic activity in the pullulanase preparation was determined by the release of 280 imx. absorbing material from acid denatured haemoglobin (Sigma no H 2500, 2 x crystallized).…”
Section: Introductionmentioning
confidence: 99%